Health Worker Support as a Key Determinant of Exclusive Breastfeeding in Indonesia - Satria Akbar Putra Asmara; Ulil Albab Habibah; Syva Sadira; Giska Aliya Levia; Iin Nurseptyani Wulandari (Jurnal Penelitian Kesehatan SUARA FORIKES, 2026)
Exclusive breastfeeding for the first six months is recommended by the World Health Organization and UNICEF because it provides optimal nutrition and immune protection for infants. However, the coverage of exclusive breastfeeding in Indonesia remains below the global target. Support from health workers is considered an important factor influencing breastfeeding practices, yet previous studies have reported inconsistent results. This study aimed to estimate the pooled effect size of the association between support from health workers and exclusive breastfeeding among infants aged 0–6 months in Indonesia, thereby providing robust empirical guidance for national maternal health policy. This systematic review and meta-analysis was conducted in March 2026 following PRISMA guidelines. A literature search was conducted in Google Scholar, PubMed, ScienceDirect, and Garuda databases for articles published between 2021 and 2026. Data analysis was performed using Review Manager 5.4 with the Odds Ratio (OR) effect size and 95% confidence interval using the Mantel–Haenszel method with a random effects model. Sensitivity analysis was performed using Review Manager 5.4. Publication bias was analyzed using funnel plots and Egger's test. A total of 11 cross-sectional studies were included in this study. Meta-analysis showed that support from health workers significantly increased the likelihood of exclusive breastfeeding [5.77 (95% CI: 3.88–8.57)]. Sensitivity analysis using the leave-one-out method demonstrated robust pooled estimates, with ORs ranging consistently from 5.39 (95% CI: 3.60–8.08) to 6.47 (95% CI: 4.13–10.14) across all iterations. Risk of bias was mostly moderate. Egger's test indicated publication bias (p = 0.0126). In conclusion, health worker support is a high-impact intervention that significantly increases exclusive breastfeeding in Indonesia. While family and sociocultural factors also play a role, structured professional support remains a primary driver of successful breastfeedingKeywords: exclusive breastfeeding; health worker support; breastfeeding counseling; maternal health services; Indonesia